The decay of Ga72 - Sulaiman, M. Yusof (Universiti Pertanian Malaysia, 1981)
The beta-decay of Ga72 was studied using 25cc., 33cc., and 6Occ. Ge(Li) detectors in singles and roincidence modes.. The latter was carried out using a dual-parameter system. many observations reported in an earlier investigation were not supported.